The Communicative Competency of Boys with Attention Deficit Hyperactivity Disorder - Terry J. Rennie (Connections 2003 pp:69-89, 2003)
Learning in the classroom requires children to meet an accepted set of language and communication standards described in the curriculum. Those children who do not meet these expectations are at a serious disadvantage. One group of children who experience difficulties are those diagnosed with attention deficit hyperactivity disorder (ADHD). The research literature on ADHD emphasizes children's problems with attention span, self-regulation and impulse control. While the literature has examined important aspects of language and ADHD, it has not looked at critical aspects of children's ability to communicate effectively. The major objectives of this study were to examine the language of children with ADHD to learn more about how they communicate. This study examined the communicative competency of a sample of 10 boys aged 6 to 9 years (5 boys with ADHD and 5 boys without ADHD). The boys were videotaped through a one-way mirror engaging the Researcher in conversations, building and playing with a Lego model. Overall, participants in both groups were similar regarding language production, phonology, and aspects of morphology and syntax. Substantial differences were found in the semantic components of grammatical competency, sociolinguistic and discourse competency. The ADHD participants had difficulty making connections beyond the "here-and-now" and using complex, abstract concepts. The Non-ADHD participants did not demonstrate such difficulties. These findings suggest that cognitive functioning is a significant factor. The finding that the ADHD participants communicated differently than the Non-ADHD participants has important implications for learning in the classroom, understanding ADHD and directions for future research.